Providers' Perceptions of Medical Interpreter Services and Limited English Proficiency (LEP) Patients: Understanding the "Bigger Picture". (September 2015) - Michalec, Barret; Maiden, Kristin M.; Ortiz, Jacqueline; Bell, Ann V.; Ehrenthal, Deborah B.
Patient's ability to understand and effectively communicate health information facilitates disease prevention, self-management of illness, the adoption of healthy behaviors, and their ability to act on important public health information. However, patients who have limited English proficiency (LEP) are significantly disadvantaged. Previous studies have shown the benefit of medical interpreter services in bridging the health communication gap between patients and providers. This qualitative study, focusing on medical interpreter utilization within obstetrical and neonatal services, provides perspectives from multiple types of providers to further explore the role of medical interpreter services and specific barriers to the use of such services. Five separate focus groups were conducted with postpartum nurses, labor and delivery/triage nurses, obstetrics and gynecology (OBGYN) resident physicians, neonatal intensive-care unit (NICU) nurses, and faculty physicians, nurse practitioners, and midwives. The data show that barriers to the utilization of professional medical interpreters can be categorized by distinct but related institutional- and individual-level factors. Further interpretation of the barriers, however, suggests that providers' use/non-use of interpreter services is merely one piece of a much "bigger picture" regarding difficulties and challenges in delivering care to a growing culturally diverse patient population, and that these cultural challenges, not just the availability of interpreter services, may affect providers' ability to deliver effective and efficient care. It is argued that simply adding additional communication-based resources may not be sufficient to impact providers' attitudes and behaviors or the overarching organizational culture regarding LEP patients.